57. clinical Characteristics and Outcomes of Patients Hospitalized with COVID-19 in New Orleans, LA: A Cohort Study. (31st December 2020) - Silver, Victoria; Chapple, Andrew; Feibus, Allison H; Beckford, Jeremy; Halapin, Natalie; Barua, Delphi; Gordon, Angellica; Baumgartner, William; Vignes, Seth; Clark, Cullen; Kamboj, Sanjay; Lim, Stephen; et al.
Abstract: Background: In Louisiana, deaths related to COVID-19 have disproportionately occurred in Black persons. Granular data are needed to better understand inequities and develop prevention strategies to mitigate further impact on Black communities. Methods: We conducted a retrospective cohort study of patients admitted to an urban safety net hospital in New Orleans, LA with reactive SARS-CoV-2 testing from March 9–31, 2020. Clinical characteristics and outcomes of Black and other racial/ethnic group patients were compared using Wilcoxon rank-sum test and Fisher's exact tests. We examined Day-14 status using an ordinal scale to assess race and outcome. Table 1. Demographics and Comorbidities by Race for Patients Hospitalized with COVID-19 Table 2. Clinical Characteristics at Presentation by Race for Patients Hospitalized with COVID-19, March 2020 Results: This study included 249 patients. Median age was 59, 44% were male, 86% were age ≥65 years or had ≥1 comorbidity. Overall, 87% were Black, relative to 55% Black patients typically hospitalized at our center. Black patients had longer symptom duration at presentation (6.41 versus 5.88 days, p=0.05), and were more likely to have asthma (p=0.008), but less likely to have dementia (p=0.002). There were no racial differences in initial respiratory status or laboratory values other than higher initial LDH in Black patients. Patient age and initial oxygen requirement, but not race (adjusted proportional odds ratio = 0.92, 95%CI: 0.70–1.20), were associated with worse Day-14 outcomes. Figure 1: Admissions over time by Race Figure 2a: Hospital outcomes by Race over the Follow-up period Figure 2b: Day-14 Outcomes by Race Conclusion: Our results demonstrate minor racial differences in comorbidities or disease severity at presentation, and Day-14 outcomes were not different between groups. However, Black patients were disproportionately represented in hospitalizations, suggesting that prevention efforts should include strategies to limit SARS-CoV-2 exposures in Black communities as one step towards reducing racial inequities related to COVID-19. Figure 3a: Logistic Regression for Initial Oxygen Requirement Figure 3b: Cumulative Logistic Regression for Ordinal Day-14 Outcomes Disclosures: Meredith E. Clement, MD, FHI360 (Consultant)Gilead (Research Grant or Support)Janssen (Scientific Research Study Investigator)